2022
DOI: 10.3390/ijms23084076
|View full text |Cite
|
Sign up to set email alerts
|

DnaJC7 in Amyotrophic Lateral Sclerosis

Abstract: Protein misfolding is a common basis of many neurodegenerative diseases including amyotrophic lateral sclerosis (ALS). Misfolded proteins, such as TDP-43, FUS, Matrin3, and SOD1, mislocalize and form the hallmark cytoplasmic and nuclear inclusions in neurons of ALS patients. Cellular protein quality control prevents protein misfolding under normal conditions and, particularly, when cells experience protein folding stress due to the fact of increased levels of reactive oxygen species, genetic mutations, or agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…DnaJC7 contains a C-terminal J domain and tetratricopeptide repeat (TPR) domains (Dilliott et al, 2022). The TRP domains are predicted to interact with Hsp90 and Hsp70 and may facilitate the flow of client proteins from Hsp70s to Hsp90s (Assimon et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…DnaJC7 contains a C-terminal J domain and tetratricopeptide repeat (TPR) domains (Dilliott et al, 2022). The TRP domains are predicted to interact with Hsp90 and Hsp70 and may facilitate the flow of client proteins from Hsp70s to Hsp90s (Assimon et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…DnaJC7 mutations cause dominantly inherited Amyotrophic Lateral Sclerosis (ALS) 24 . 17 mutations have been identified that are distributed across all domains of DnaJC7 (Figure 5C).…”
Section: Disease-associated Dnajc7 Mutations Differentially Modulate ...mentioning
confidence: 99%
“…Instead of destabilizing DnaJC7, these mutations exhibit gain-of-function effects likely through dysregulation of interactions within the chaperone network. Disease-associated mutations occur in both DnaJC7 and DnaJB6 24,30,31 . This suggests that DnaJB6, DnaJC7 and other JDPs are not functionally redundant.…”
Section: Disease-associated Mutations Of Dnajc7 Differentially Affect...mentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, there is intense, ongoing research on ALS, which is leading to interesting findings [ 10 ].…”
mentioning
confidence: 99%